2012
DOI: 10.1007/bf03353686
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis and Photocatalytic Property of Zinc Oxide Nanoparticles

Abstract: Zinc oxide (ZnO) nanoparticles of varying sizes (20, 44 and 73 nm) have been successfully synthesized by a hybrid electrochemical-thermal method using aqueous sodium bicarbonate electrolyte and sacrificial Zn anode and cathode in an undivided cell under galvanostatic mode at room temperature. The as-synthesized product was characterized by X-ray diffraction (XRD), X-ray photoelectron spectra (XPS), Scanning electron microscopy along with Energy dispersive analysis of X-ray (SEM/EDAX), Transmission electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(44 citation statements)
references
References 34 publications
4
36
0
1
Order By: Relevance
“…In the XPS spectrum of ZnIn 2 S 4 , the Zn 2p signals were observed at binding energies (BEs) of 1022.18 (Zn 2p 3/2 ) and 1045.24 eV (Zn 2p 1/2 ), in good agreement with a previous report, whilst the Zn 2p core‐level spectrum of ZnIn 2 S 4 –VS 2 exhibited signals at 1021.54 (Zn 2p 3/2 ) and 1044.54 eV (Zn 2p 1/2 ). Two Zn 2p shake‐up satellite peaks were also observed at 1025.27 and 1048.38 eV for ZnIn 2 S 4 and at 1023.66 and 1046.51 eV for ZnIn 2 S 4 –VS 2 .…”
Section: Resultssupporting
confidence: 90%
“…In the XPS spectrum of ZnIn 2 S 4 , the Zn 2p signals were observed at binding energies (BEs) of 1022.18 (Zn 2p 3/2 ) and 1045.24 eV (Zn 2p 1/2 ), in good agreement with a previous report, whilst the Zn 2p core‐level spectrum of ZnIn 2 S 4 –VS 2 exhibited signals at 1021.54 (Zn 2p 3/2 ) and 1044.54 eV (Zn 2p 1/2 ). Two Zn 2p shake‐up satellite peaks were also observed at 1025.27 and 1048.38 eV for ZnIn 2 S 4 and at 1023.66 and 1046.51 eV for ZnIn 2 S 4 –VS 2 .…”
Section: Resultssupporting
confidence: 90%
“…1, zinc oxide (ZnO) has significant importance in the field of the heterogeneous photocatalysis, and then, the physicochemical properties of ZnO and therefore its application also depend on its synthesis route. Although ZnO has been synthesized in the film form by a variety of methods, the electrochemical technique for the synthesis of nanosized metal oxide films has acquired a considerable interest because of its simplicity, low operating temperature, and viability for commercial production (Wang et al 2011b;Chandrappa and Venkatesha 2012).…”
Section: Direct Oxidation Methodsmentioning
confidence: 99%
“…The crucial degradation efficiency after 80 min illumination has changed a little compared with the efficiency obtained after the initial illumination for 20 min. The relative bigger size and the reduction of the number of surface hydroxyl are the main reasons for the decrease of degradation efficiency of photocatalysts [37]. The increase of particle size with increased calcination temperature to 600℃ (Fig.…”
Section: Influence Of Calcination Temperature On Zto Photocatalystsmentioning
confidence: 99%
“…It has been shown that dyes can be easily adsorbed and catalyzed on oxide surfaces. However, to the best of our knowledge, there exist only a few reports [33][34][35][36][37] on the direct removal of commonly used industrial dyes. In the present investigation, we focus on the bulk synthesis of cubic shaped ZTO nanoparticles with a hybrid electrochemical-thermal route without using any template or surfactant at room temperature.…”
Section: Introductionmentioning
confidence: 99%